Concepções de professores dos anos iniciais sobre alfabetização e letramento científico - Silva, Valéria Gomes Campos da (2019)
Scientific literacy has as an objective the promotion of skills and competencies in students to enable them participation and active decision-making in everyday activities and develop their critical thinking. Learners can make use of this knowledge to engage in discussions about the world around them with a critical view about it. Scientific knowledge is connected to all aspects of one’s life regardless of their educational background or occupation. Everyone is immersed in the same reality and there is a greater need to better understand Science and its implications. Teachers act as mediators of the literacy process and they are responsible for clarifying the scientific concepts for learners and raise their awareness of its importance. It is known that primary year students are already able to take part in discussions about scientific themes, therefore the importance of scientific literacy in teacher development programs and for students. The focus of this research was to investigate primary teachers’ conceptions regarding scientific literacy and its implications in their daily practice. This research is of utmost importance for the professional development of primary teachers as it is understood that this development will be more effective if it has a solid basis of scientific knowledge. The objectives are: identify what primary teachers understand about scientific literacy and assess if this understanding and their practice enable the development of the scientific literacy of their students. This is a qualitative research that used an open questionnaire with 133 teachers from the city of Ribeirao Pires in São Paulo. The results have shown that elementary teachers’ conceptions of literacy are much more related to language literacy (in this case Portuguese) than with scientific literacy. Although this concept has been in discussion since the middle of the 20th century, it is not part of teachers’ professional development. It is possible to assume that misconceptions around this subject have a direct implication on their professional qualification and on their teaching practice.